Preparation, Characterization, and Bioactivity Evaluation of Polyoxymethylene Copolymer/Nanohydroxyapatite-g-Poly(ε-caprolactone) Composites - Kinga Pielichowska; Paula Szuba; Joanna Maciocha; Beata Macherzyńska; Katarzyna Nowicka; Piotr Szatkowski (Nanomaterials, 2022)
In this work, nanohydroxyapatite (HAp) was functionalized with poly(ε-caprolactone) (PCL), using 1,6-hexamethylene diisocyanate (HDI) as a coupling agent, and then incorporated into the polyoxymethylene copolymer (POM) matrix using the extrusion technique. The obtained POM/HAp-g-PCL composites were investigated using FTIR, DSC, TOPEM DSC, and TG methods. Mechanical properties were studied using destructive and non-destructive ultrasonic methods, wettability, and POM crystallization kinetics in the presence of HAp-g-PCL. Moreover, preliminary bioactivity evaluation of the POM/HAp-g-PCL composites was performed using the Kokubo method. It was found that the introduction of HAp-g-PCL to the POM matrix has a limited effect on the phase transitions of POM as well as on its degree of crystallinity. Importantly, HAp grafted with PCL caused a significant increase in the thermal stability of the POM, from 292 °C for pristine POM to 333 °C for POM modified with 2.5% HAp-g-PCL. If unmodified HAp was used, a distinct decrease in the thermal stability of the POM was observed. Crystallization kinetic studies confirmed that HAp-g-PCL, in small amounts, can act as a nucleating agent for the POM crystallization process. Moreover, incorporation of HAp-g-PCL, although slightly decreasing the mechanical properties of POM composites, improved the crucial parameter in biomedical applications, namely the in vitro bioactivity.